2004
DOI: 10.1016/j.jvs.2004.06.026
|View full text |Cite
|
Sign up to set email alerts
|

Transcervical carotid stenting with internal carotid artery flow reversal: Feasibility and preliminary results

Abstract: Transcervical CAS with carotid flow reversal is feasible and safe. It can be done with the patient under local anesthesia, averts the complications of the transfemoral approach, and eliminates the increased complexity and cost of cerebral protection devices. Transcervical CAS is feasible when the transfemoral route is impossible or contraindicated, and may be the procedure of choice in a subset of patients in whom carotid stenting is indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
43
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 33 publications
1
43
0
Order By: Relevance
“…It eliminates some of the complications associated with the transfemoral route, which include the hazards of wire and catheter manipulation in the aortic arch. In this setting, Criado et al described in 2004 a technique for transcervical CAS with flow reversal protection [65]. Although the experience is still small and prospective trials are needed, the short-term and long-term outcomes are also good and appear comparable with the reported results for carotid revascularization by endarterectomy [66,67].…”
Section: Embolic Protection Devices (Epd)mentioning
confidence: 90%
“…It eliminates some of the complications associated with the transfemoral route, which include the hazards of wire and catheter manipulation in the aortic arch. In this setting, Criado et al described in 2004 a technique for transcervical CAS with flow reversal protection [65]. Although the experience is still small and prospective trials are needed, the short-term and long-term outcomes are also good and appear comparable with the reported results for carotid revascularization by endarterectomy [66,67].…”
Section: Embolic Protection Devices (Epd)mentioning
confidence: 90%
“…[11][12][13][14][15][16] In the first technique, the carotid lesion is crossed unprotected, and in the second technique, one prolonged retrograde flow may produce brain damage. In a recent study, we have managed to reduce the time of flow reversal only for the time required to cross the ICA lesion for the insertion of the carotid filter (mean time 1.5 minutes) and this has made this technique applicable to patients with reduced intracranial collaterals and occlusion of the opposite ICA.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16][17] Using this technique in a series of 48 octogenarians unsuitable for transfemoral CAS, Faraglia et al 9 has reported a 2.1% incidence of ischemic events and 13.8% incidence of intraoperative embolization rates, measured by diffusion-weighted-magnetic resonance imaging (DW-MRI). 9 Palombo et al 10 compared filter protected transcervical with transfemoral CAS and have found a significant decrease in transient ischemic attacks (TIAs) and stroke (2.3% vs 19.8%; P Ͻ .01), as well as postprocedure brain embolization in DW-MRI (14.3% vs 36.8%; P ϭ .015) after the transcervical procedure.…”
mentioning
confidence: 99%
See 2 more Smart Citations